Mycosis fungoides and Kaposi's sarcoma association in an HIV-negative patient - Maria Carolina Prado Fleury Bariani; Luiz Fernando Fróes Fleury Júnior; Ana Maria Quinteiro Ribeiro; Siderley de Souza Carneiro; Tiago Arantes Pereira (Sociedade Brasileira de Dermatologia, 2016)
Abstract The association of mycosis fungoides and kaposi's sarcoma in HIV-negative patients is a rare phenomenon. The presence of human herpesvirus 8 (HHV-8) - associated with all forms of Kaposi's sarcoma - has also been recently identified in mycosis fungoides lesions. However, a causal association between HHV-8 and the onset of mycosis fungoides has not been established yet. The present case reports a patient who developed Kaposi's sarcoma lesions after a two-year UVB phototherapy to treat a mycosis fungoides. Negative immunohistochemistry staining for Kaposi's sarcoma-associated herpesvirus in the initial mycosis fungoides lesions strengthens the absence of a link between Kaposi's sarcoma-associated herpesvirus and mycosis fungoides. Immunosuppression caused by the lymphoma and prolonged phototherapy were probably the contribut ing factors for the onset of Kaposi's sarcoma.